2013
DOI: 10.4067/s0718-19572013000100011
|View full text |Cite
|
Sign up to set email alerts
|

Variabilidad estacional de la clorofila a y su respuesta a condiciones El Niño y La Niña en el Norte del Golfo de California

Abstract: El Niño Austral Oscillation). We propose that shifts from a strong El Niño (1997Niño ( -1998 to La Niña conditions (1999), the phytoplankton biomass response was low because a great oceanography conditions changes (wind, stability, etc.), however with the shifts from El Niño weak (2009)(2010) to La Niña (2011), these conditions represent less stress with a suitable phytoplankton response and the biomass increases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 26 publications
1
12
0
1
Order By: Relevance
“…Santamaría-del Angel et al [10] also reported that this Chl a concentration was associated with areas with a high upwelling effect and also a high concentration of photosynthetic pigments. The Chl a values in the north region were similar to the ones observed in the central region, which happened despite being an area where high concentrations of nutrients exist by the occurrence of upwelling effects and tidal mixing processes [6,10,30] in a very shallow area (<30 m) [5]; in combination with turbulence, inorganic nutrients, terrigenous types, and total matter in suspension, high turbidity levels were developed.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Santamaría-del Angel et al [10] also reported that this Chl a concentration was associated with areas with a high upwelling effect and also a high concentration of photosynthetic pigments. The Chl a values in the north region were similar to the ones observed in the central region, which happened despite being an area where high concentrations of nutrients exist by the occurrence of upwelling effects and tidal mixing processes [6,10,30] in a very shallow area (<30 m) [5]; in combination with turbulence, inorganic nutrients, terrigenous types, and total matter in suspension, high turbidity levels were developed.…”
Section: Discussionsupporting
confidence: 64%
“…In addition, the effects of El Niño 2009-2010 and 2015-2016 events were observed to have a significant effect on the Chl a annual variability and causing a decrease in its concentration during these events. On the other hand, the SOI index and Chl a time series showed a strong correlation from 2002 to 2009, and a delayed response was observed from 2010 to 2019, developing a not strong correlation between both time series associated with the moderate El Niño events during 2009 persisting in 2019 due to the very strong El Niño in 2015 [30,55].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Even though river pulse-flows have reached the ocean only sporadically and briefly for over 50 years, the upper Gulf of California continues to be an important area for marine primary productivity, with chlorophyll-a values as high as 18.2 mg m −3 (Millán Núñez et al, 1999) and average values of about 1.8 mg m −3 during 1997 to 2007(Pérez Arvizu et al, 2013. Therefore, despite the lack of river waters, the coastal high productivity is assumed to remain active by the addition of nutrients, of which Si is also a major nutrient for marine diatoms.…”
Section: Introductionmentioning
confidence: 99%
“…Because these are immature fish, the observed differences may be associated to diet and nutrition. During winter and spring, higher primary productivity has been reported in the northern part of the Gulf of California ( Pérez-Arvizu, Aragón-Noriega & Espinosa-Carreón, 2013 ); which suggests greater food abundance and diversity for the organisms that live there, including totoaba. Although juvenile totoaba consume diets with high protein levels and moderate lipid content, their natural diet seems to be rich in Ω-3 and Ω-6 highly unsaturated fatty acids (HUFAs) ( López et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%